The Correlation between Human papillomavirus and Increased Expression of p53 in Seborrheic Keratosis - Fesdia Sari; Sri Lestari; Rina Gustia; Ennesta Asri; Tofrizal Tofrizal (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Seborrheic keratosis is a benign epidermal skin tumor caused by sun exposure, virus, and genetic factor. Human papillomavirus (HPV) infection presumed to have an important role in seborrheic keratosis. Protein p53 is a protein produced by tumor suppressor gene. There has been no research that correlates of HPV with p53 increase in seborrheic keratosis. Purpose: To prove the correlation between HPV and increased p53 expression in seborrheic keratosis. Methods: This study is an analytic cross-sectional comparative study. Samples were taken using a consecutive sampling method. There were 22 seborrheic keratosis patients recruited as the research sample. HPV were detected using the polymerase chain reaction (PCR), and p53 expression were detected using the immunohistochemistry examination. Result: The mean age of seborrheic keratosis patients in this study was 54.36±10.09 years, and they were predominantly males (54.5%). HPV were found in 86.4% of the seborrheic keratosis patients. The P53 expression (+) were 77.3%, (++) were 13.6%, and (+++) were 9.1%. All of the seborrheic keratosis with increased  p53 expression had positive HPV results, but with no significant results (p=0.600). Conclusion: There were no correlation between HPV with increased  p53 expression in seborrheic keratosis patients.